Therapy of Acute Intestinal Infections in Children: Proven Efficiency - S. V. Khaliullina; V. A. Anokhin (Журнал инфектологии, 2014)
The paper focuses on questions of etiotropic, pathogenetic, and symptomatic treatment of acute infectious diarrhea in children. The recommendations are given with the basic principles of evidence-based medicine including summary data from randomized clinical trials and metaanalyses. The new lines of the treatment are discussed such as the possibility of application of antiemetic, antidiarrheal, antisecretory, probiotic drugs in pediatric practice.